Efforts to Improve Learning Outcomes of Islamic Religion Lessons for Class III Students Through the Role Playing Method (International Journal of Education and Literature, 2023)
The aim of this research is to describe the learning outcomes of Class III Students' Islamic Religion through the Role Playing Method. The type of research used in this case is in the form of classroom activities and is descriptive in nature with quantitative techniques. From the results of Classroom Action Research (CAR), student learning outcomes can be improved by using role-playing techniques in learning Islamic Religion. The highest scores, averages, and completion rates of students in each cycle, indicating substantial results. The highest scores obtained per cycle were 80; 90; 100, average 58.70; 69.78; 82.61 and completeness 48; 78.26; 87%.